Retinoic acid expression associates with enhanced IL-22 production by γδ T cells and innate lymphoid cells and attenuation of intestinal inflammation - Mielke, Lisa A. (The Rockefeller University Press, 2013)
Retinoic acid (RA), a vitamin A metabolite, modulates mucosal T helper cell responses. Here we examined the role of RA in regulating IL-22 production by γδ T cells and innate lymphoid cells in intestinal inflammation. RA significantly enhanced IL-22 production by γδ T cells stimulated in vitro with IL-1β or IL-18 and IL-23. In vivo RA attenuated colon inflammation induced by dextran sodium sulfate treatment or Citrobacter rodentium infection. This was associated with a significant increase in IL-22 secretion by γδ T cells and innate lymphoid cells. In addition, RA treatment enhanced production of the IL-22–responsive antimicrobial peptides Reg3β and Reg3γ in the colon. The attenuating effects of RA on colitis were reversed by treatment with an anti–IL-22 neutralizing antibody, demonstrating that RA mediates protection by enhancing IL-22 production. To define the molecular events involved, we used chromatin immunoprecipitation assays and found that RA promoted binding of RA receptor to the IL-22 promoter in γδ T cells. Our findings provide novel insights into the molecular events controlling IL-22 transcription and suggest that one key outcome of RA signaling may be to shape early intestinal immune responses by promoting IL-22 synthesis by γδ T cells and innate lymphoid cells.